ANALISIS PENGUATAN PRILAKU JUJUR DAN TANGGUNG JAWAB ANAK USIA 5–6 TAHUN MELALUI PEMANFAATAN MEDIA AUDIO VISUAL DI PAUD RINJANI UNRAM - Nurholiza Izzati; Titin Astuti; Ida Ermiana; Darmiany (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aims to examine the use of audio-visual media in strengthening honest and responsible behavior among children aged 5–6 years at PAUD Rinjani UNRAM. Honesty and responsibility are essential aspects of moral and character development that need to be instilled from an early age. However, in practice, some children still have difficulty consistently demonstrating honest behavior and taking responsibility for their tasks and obligations. Therefore, engaging and age-appropriate learning media are needed, one of which is audio-visual media. This study employed a qualitative approach using a descriptive method. The research subjects consisted of teachers and children aged 5–6 years at PAUD Rinjani UNRAM. Data were collected through observation, interviews, and documentation. The collected data were analyzed through data reduction, data presentation, and conclusion drawing. The findings revealed that the use of audio-visual media helped children understand the values of honesty and responsibility through interesting, concrete, and easily understandable content. Children showed improvements in honest behavior, such as admitting mistakes and telling the truth. In addition, they demonstrated greater responsibility by tidying up learning materials after use, completing assigned tasks, and following classroom rules. The teacher’s role in providing explanations, reinforcement, and positive role modeling after the presentation of audio-visual media also contributed significantly to the success of character strengthening. In conclusion, the use of audio-visual media is an effective learning tool for strengthening honest and responsible behavior among children aged 5–6 years at PAUD Rinjani UNRAM.